2010
DOI: 10.1515/jib-2010-149
|View full text |Cite|
|
Sign up to set email alerts
|

Towards Prediction and Prioritization of disease genes by the modularity of human phenome-genome assembled network

Abstract: SummaryEmpirical clinical studies on the human interactome and phenome not only illustrates prevalent phenotypic overlap and genetic overlap between diseases, but also reveals a modular organization of the genetic landscape of human disease, provding new opportunities to reduce the complexity in dissecting the phenotype-genotype association. We here introduce a network-module based method towards phenotype-genotype association inference and disease gene identification. This approach incorporates protein-protei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 18 publications
(31 reference statements)
0
6
0
Order By: Relevance
“…Regarding the applications, when a network and a set of characteristics are given, it is straightforward to compute for each characteristic the point of maximum degeneration D = H = 1, the values D, H and through the use of the four bounds, D min , D max , H min and H max . This approach can be useful in many applications, such as in [19], [20], [21] and [31] where the phase diagram is hard to compute. In such contexts statistical approaches are used to gather information on the correlation between nodes' characteristics and the network topology by looking for the relative distance of the point (D, H) from the point of maximum degeneration.…”
Section: Bounds' Implications On Dyadic Effect and Its Applicationsmentioning
confidence: 99%
See 2 more Smart Citations
“…Regarding the applications, when a network and a set of characteristics are given, it is straightforward to compute for each characteristic the point of maximum degeneration D = H = 1, the values D, H and through the use of the four bounds, D min , D max , H min and H max . This approach can be useful in many applications, such as in [19], [20], [21] and [31] where the phase diagram is hard to compute. In such contexts statistical approaches are used to gather information on the correlation between nodes' characteristics and the network topology by looking for the relative distance of the point (D, H) from the point of maximum degeneration.…”
Section: Bounds' Implications On Dyadic Effect and Its Applicationsmentioning
confidence: 99%
“…The dyadic effect has been considered in order to assess the functional role of nodes within biological networks such as, for instance, in gene-gene interaction in statistical epistasis networks [19], in phenome-genome networks [20] in disease-phenotype network [21] and in protein-protein interaction networks [31] where numerous characteristics are studied to evaluate genetic interactions. Nodes' characteristics are investigated also in interorganizational innovation networks ( [12], [14]) where partnerships agreements of technological transfer among countries are related to innovation indices.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…New network-based classification methods, such as the human disease network, also known as "diseasome" 54 (Figure 1), have found that disorders should be grouped neither by symptom nor single gene mutations but based on clusters of underlying physiologic dysfunction related to multiple simultaneous genetic polymorphisms and epigenetic changes. [54][55][56][57][58][59][60][61][62] From the clinical perspective, this helps explain why two patients with an "identical" cancer-of the breast, for example-will have different responses to identical chemotherapy regimens. A landmark study of 2000 specimens of breast cancer suggests that it can be subclassified into 10 distinct groups based on various genomic and transcriptomic properties.…”
Section: -Leroy Hood Et Al Institute For Systems Biologymentioning
confidence: 99%
“…Though it is capable of yielding biological insight in several case studies (e.g. [4] [5] [6] ), a major drawback of the community detection algorithm is the resolution limit problem [7] [8] which results in huge modules with large numbers of genes (e.g., in [5] ). Such problem is serious in disease module identification since it will inevitably introduce a lot of false disease genes (hence low specificity) and consequently adds difficulties to validation and interpretation.…”
Section: Introductionmentioning
confidence: 99%